Gestão de resíduos sólidos escolares no âmbito da Superintendência Regional de Educação de Palmas-TO - Queiroz, Samuel Silva Cardoso (2024)
Solid waste management from the perspective of environmental governance has presented itself as one of the factors for ensuring that effective management, protection, and environmental preservation actions are developed. The environmental responsibility of public administration is widely discussed and is grounded in Article 225 of the Brazilian Constitution of 1988, which, by guaranteeing the fundamental right to an ecologically balanced environment, obliges not only the private sector but also the Public Power to defend and preserve it. In this context, the present study focuses on analyzing environmental and solid waste management within the scope of the Secretariat of Education of Tocantins and the Regional Superintendence of Education of Palmas-TO. The research was developed with a qualitative approach, as it proposed to analyze solid waste management in school units to produce reflections and information on the topic. Regarding data collection techniques, documentary and bibliographic methods were used to obtain information such as concepts, characteristics, and descriptions of environmental and solid waste management in school units of the State Education System of Tocantins, focusing on those under the jurisdiction of the SRE of Palmas-TO. This study recognized the need to implement a central policy for the environmental management of school units through educational policies and also enabled the identification of strategies for solid waste management in school units through an Action Plan for the implementation of waste disposal and selective collection in School Units.